2021
DOI: 10.3389/fpsyg.2021.724675
|View full text |Cite
|
Sign up to set email alerts
|

The Relations of Parental Autonomy Support, Parental Control, and Filial Piety to Chinese Adolescents’ Academic Autonomous Motivation: A Mediation Model

Abstract: This study attempted to examine the mediating role of filial piety in the relationships between parental autonomy support and control and Chinese adolescents’ academic autonomous motivation. A set of questionnaires were administered to 492 adolescent students at two senior high schools in Fuzhou, China. Confirmatory Factor Analysis and Structural Equation Modeling were employed to analyze the data. The results showed that reciprocal filial piety (RFP) fully mediated the relationships of parental autonomy suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The results verified Hypothesis 2, showing that parental autonomy support was positively associated with filial piety, which, in turn, was negatively related to PIU. These results were consistent with research on adolescents showing that filial piety plays a mediating role between parental autonomy support and individual psychosocial development [ 36 , 37 ]. There are several possible interpretations of the findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results verified Hypothesis 2, showing that parental autonomy support was positively associated with filial piety, which, in turn, was negatively related to PIU. These results were consistent with research on adolescents showing that filial piety plays a mediating role between parental autonomy support and individual psychosocial development [ 36 , 37 ]. There are several possible interpretations of the findings.…”
Section: Discussionsupporting
confidence: 92%
“…Generations of Chinese, even in contemporary Chinese societies [ 34 , 35 ], have emphasized the importance of filial piety, which plays a critical role in family heritage and maintaining the social order. Although previous studies have not verified the mediating role of filial piety in the association between parental autonomy support and PIU, relevant studies have shown that filial piety plays a mediating role between parental autonomy support and adolescents’ psychosocial functions [ 22 , 36 ]. This can be explained by SDT [ 15 ], suggesting that parental autonomy support could fulfill individuals’ need for autonomy.…”
Section: Introductionmentioning
confidence: 99%
“…Third, instruments measuring filial piety were old, and not specifically applicable in the U.S. Existing studies have yielded mixed results regarding the effect of filial piety in caregiving outcomes [ 54 , 66 , 90 , 91 ]. Finally, given that Kramer’s caregiver adaptation conceptual model has not been tested, the proposed operational framework needs more evidence to support the hypothesis of benefits in the appraisal of caregiver outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative data revealed that nursing students felt pressure to meet their parents’ expectations and feared disappointing them. The emphasis on filial piety, which highlights the importance of family relationships and obedience to parents and elders, is a core value in Chinese culture ( Guo et al, 2021 ). This cultural context may help explain why, despite having an easier course load in year 3 compared to year 2, nursing students still experienced stress if they anticipated academic failure.…”
Section: Discussionmentioning
confidence: 99%